Assessing the Role of Shape and Label in the Misleading Packaging of Food Imitating Products: From Empirical Evidence to Policy Recommendation - Basso, Frédéric; Bouillé, Julien; Le Goff, Kévin; Robert-Demontrond, Philippe; Oullier, Olivier (Frontiers in Psychology, 2016)
Food imitating products are chemical consumer items used frequently in the household for cleaning and personal hygiene (e.g., bleach, soap, and shampoo), which resemble food products. Their containers replicate elements of food package design such as possessing a shape close in style to drinking product containers or bearing labels that depict colourful fruits. In marketing, these incongruent forms are designed to increase the appeal of functional products, leading to chemical consumer product embellishment. However, due to the resulting visual ambiguity, food imitating products may expose consumers to the risk of being poisoned from ingestion. Thus, from a public health perspective, food imitating products are considered dangerous chemical products that should not be sold, and may merit being recalled for the safety of consumers. To help policymakers address the hazardous presence of food imitating products, the purpose of this article is to identify the specific design features that generate most ambiguity for the consumer, and therefore increase the likelihood of confusion with foodstuffs. Among the visual elements of food packaging, the two most important features (shape and label) are manipulated in a series of three lab studies combining six Implicit Association Tests (IATs) and two explicit measures on products’ drinkability and safety. IATs were administered to assess consumers’ implicit association of liquid products with tastiness in a within-subject design in which the participants (N=122) were presented with two kinds of food imitating products with a drink shape or drink label compared with drinks (experiential products with congruent form) and classic chemical products (hygiene products) (functional products with congruent form). Results show that chemical consumer products with incongruent drink shapes (but not drink labels) as an element of food package design are both implicitly associated with tastiness and explicitly judged as safe and drinkable. These results require confirmation in other studies involving different shapes and labels. Notwithstanding, due to the misleading effect of this ambiguity, public health authorities are thus well advised to focus their market surveillance on chemical products emulating a food or drink shape.